Degradation of perovskite thin films and solar cells with candle soot c/ag electrode exposed in a control ambient - Islam M.A.; Mohafez H.; Sobayel K.; Hatta S.F.W.M.; Hasan A.K.M.; Khandaker M.U.; Akhtaruzzaman M.; Muhammad G.; Amin N. (MDPI, 2023)
Perovskite solar cells (PSCs) have already achieved efficiencies of over 25%; however, their instability and degradation in the operational environment have prevented them from becom-ing commercially viable. Understanding the degradation mechanism, as well as improving the fabrication technique for achieving high?quality perovskite films, is crucial to overcoming these short-comings. In this study, we investigated details in the changes of physical properties associated with the degradation and/or decomposition of perovskite films and solar cells using XRD, FESEM, EDX, UV?Vis, Hall?effect, and current?voltage (I?V) measurement techniques. The dissociation, as well as the intensity of perovskite peaks, have been observed as an impact of film degradation by humidity. The decomposition rate of perovskite film has been estimated from the structural and optical changes. The performance degradation of novel planner structure PSCs has been investigated in detail. The PSCs were fabricated in?room ambient using candle soot carbon and screen?printed Ag electrode. It was found that until the perovskite film decomposed by 30%, the film properties and cell efficiency remained stable. 2021 by the authors. Licensee MDPI, Basel, Switzerland.